A Analysis of A Geologically Controlled Groundwater Basin: Major Ion Chemistry and Groundwater Flow Patterns on The Eastern Slope of Mount Gede Cianjur West Java - Rina Rosmawati; T. Yan W. M. Iskandarsyah; Faishal Aziz; Wahyudi; Mochamad Nursiyam Barkah; Yudhi Listiawan; Hendarmawan (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Population growth is directly proportional to the increasing demand for water, while land-use changes into residential areas also affect the region’s water storage capacity. In Cianjur Regency, residents’ water needs are supplied by the Cianjur and Cibanteng sub-watersheds (Sub-DAS), most of which have undergone land conversion into settlements. This condition highlights the importance of studying groundwater flow systems to ensure the sustainability of water resources. Geologically, the area consists of old volcanic rocks and younger volcanic deposits, with permeability values ranging from 5.789×10⁻³ to 1.8752×10⁻⁷ cm/sec. Based on physical properties, groundwater shows different characteristics within a groundwater basin, EC and TDS values tend to increase downstream, indicating groundwater interaction. Chemically, the groundwater exhibits facies containing Mg-Ca, HCO₃ minerals, suggesting that the groundwater is in a transitional flow phase. The relatively high Mg/Ca ratio indicates that evaporation plays a significant role in controlling groundwater chemistry. The Ca-Mg or Ca/Mg phase forms due to dissolution processes from evaporation and prolonged interaction between water and older rocks. This phenomenon provides important insights into the dynamics of the groundwater flow system in Cianjur. The development of this groundwater flow is crucial for water resource planning and management in Cianjur Regency.